Implementasi Game Math Puzzle sebagai Media Pembelajaran Numerasi Siswa SDN 02 Badrain - Nurhadiani, Rina; Alifa, Siti; Aisy, Rihadatul; Satira, Satira; Katrunada, Saskia; Humaela Rizka, Siti; Chandra Dewi, Alfiana; Dwi Astuti, Silvia (Rengganis Jurnal Pengabdian Masyarakat, 2024)
School with relatively low literacy and numeracy skills are an indicator of where campus teaching programs are held. Therefore, students from the Faculty of Teacher Training and Education at the University of Mataram who were registered as campus teaching participants for grade 6th placement at SDN 02 Badrain created the "Math Puzzle Game" program. The aim of this program is to improve students' numeracy skills through the application of math puzzle games which are expected to be a fun learning medium as well as improving problem solving skills, sharpening logical skills, strengthening number understanding abilities, and encouraging teamwork. The target of this program is students in grades 4, 5, and 6. The method for implementing the "math puzzle game" program uses several stages, namely preparation, implementation, and evaluation or improvement. The results of applying the math puzzle game are that students have the ability to think quickly and critically when solving puzzles, students understand basic mathematical concepts, and students succeed in applying their understanding of the relationship between numbers and solving mathematical problems correctly. It is hoped that this service can be continued and carried out more optimally in the future learning process. Seeing the aim of service through this program is very important as an effort to improve students' numeracy skills.